Determinants of Economic Value Addition of Industrial Tuna Fish Processors in the Sea Food Processing Sub-Chain in Malaysia - Haiqal Alif Ramadhan (Journal of Economics Business Industry, 2023)
Value added is the difference between the output value, input material, and processing costs. The supply chain of tuna products is inseparable from production costs as a support for increasing the added value potential of fish. This study aims to determine the added value of supply chain entities as a whole for each alternative using the Hayami method and determine the level of marketing efficiency of existing supply chain flows using farmer's share analysis for this added value, using the Hayami method to find out which tuna product is the most profitable to increase the added value of this tuna. The tuna supply chain actors consist of fishermen as fish producers, transit docks, fresh tuna processing industries, canned tuna processing industries, tuna fillet processing industries, traditional market traders, supermarkets, export agents, and consumers. The added value obtained by fishing entities is MYR (Ringgit Malaysia) 1,061, with an added value ratio of 4.38% for one fish production, amounting to MYR 20,758 or 45.67%, a canned tuna processing entity of MYR 5,940 or 19.6%, a tuna fillet processing entity of MYR 8,485 or 25.91%, a traditional market trader entity of MYR 3,758 or 24.8%, canned tuna supermarket entity of MYR 561 or 15.41% tuna fillet supermarket entity in the amount of MYR 107 or 3.05% and an export agent entity of MYR 15,151 with a value-added ratio of 25%. Of all the entities that get the most significant added value, the fresh tuna processing entity amounting to MYR 20,758 per week.